TEACHER TRAINING PROGRAMS, GUAM AND TAIWAN: A COMPARATIVE STUDY - Dean Olah (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This study provides an in-depth comparative analysis of the teacher preparation systems in Guam and Taiwan, examining two distinct models for training K-12 educators. Guam's system mirrors the decentralized, university-led model of the United States, which is regulated by professional accreditation and standardized testing. In contrast, Taiwan utilizes a centralized, state-controlled model featuring a national curriculum, a mandatory internship after graduation, and a high-stakes national qualifying examination. Using a qualitative comparative case study design, this research analyzes policy documents, university curricula, and academic literature to understand the historical and cultural foundations of each system. The findings show fundamental differences in licensure pathways, curriculum philosophy, the structure of clinical practice, and certification assessments. While Guam's approach allows for flexibility and local adaptation, Taiwan's ensures national uniformity and quality control. The study concludes that neither model is definitively superior, as their effectiveness depends on their specific context. The paper proposes actionable recommendations, suggesting that Guam could benefit from developing a more holistic, performance-based capstone assessment. For Taiwan, it recommends granting universities greater curricular autonomy and diversifying the certification process. Ultimately, this research contributes to the field of comparative education by detailing the trade-offs between decentralized and centralized approaches to teacher preparation.